2007
DOI: 10.3748/wjg.v13.i20.2791
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of nuclear matrix-intermediate filament system and differential expression of nuclear matrix proteins during human hepatocarcinoma cell differentiation

Abstract: AIM:To investigate the association between the configurational and compositional changes of nuclear matrix and the differentiation of carcinoma cells. METHODS:Cells cultured with or without 5 × 10 -3 mmol/L of hexamethylene bisacetamide (HMBA) on Nickel grids were treated by selective extraction and prepared for whole mount observation under electron m i c ro s c o p y. T h e s a m p l e s w e re e x a m i n e d u n d e r transmission electron microscope. Nuclear matrix proteins were selectively extracted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…However, in our study, the functions and mechanisms of Bβ10-42 in the procedure of HBV related liver diseases are still not explicit. NPM, an established marker for the granular components [32,33], can cause the suppression of cell differentiation and anti-apoptosis in human carcinogenesis, especially in hepatocellular carcinoma [34][35][36]. NPM decreased during HBV infection and the mechanism should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the functions and mechanisms of Bβ10-42 in the procedure of HBV related liver diseases are still not explicit. NPM, an established marker for the granular components [32,33], can cause the suppression of cell differentiation and anti-apoptosis in human carcinogenesis, especially in hepatocellular carcinoma [34][35][36]. NPM decreased during HBV infection and the mechanism should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosone-associated SIN3B was thus proved important in PTEN-induced cell senescence and thereto prevented progression to invasive prostate adenocarcinoma. In human hepatocarcinoma cells (HCC), SIN3B was upregulated in the hexamethylene bisacetamide (HMBA)-induced differentiation ( Tang et al, 2007 ). But the expression levels of MAD1, the member of MXD family, reduced in HCC tissues ( Nam et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found NPM was a nuclear matrix protein and its expression was downregulated in the induced differentiation of human osteosarcoma, human neuroblastoma tumors and human liver cancer (6)(7)(8), indicating NPM functioned in regulating the differentiation of tumor cells (9). Liver cancer is the most common malignant gastrointestinal cancer and the screening for functional proteins related to liver tumor cell differentiation will contribute to the elucidation of the mechanism of liver cancer development and its early diagnosis.…”
Section: Introductionmentioning
confidence: 99%